2019
DOI: 10.1097/ncc.0000000000000699
|View full text |Cite
|
Sign up to set email alerts
|

What Are the Experiences of Men Affected by Prostate Cancer Participating in an Ecological Momentary Assessment Study?

Abstract: Background Within the cluster of self-report methodologies, ecological momentary assessment (EMA) is a method used in health services research whereby a participant repeatedly reports on affect, behaviors, symptoms, and cognitions as they occur in real time in the participant’s natural environment. However, little is known about the impact of participating in an EMA study on individuals’ experiences who are affected by prostate cancer. Objectives The ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 36 publications
2
12
0
Order By: Relevance
“…The predicted decrease from 4.4s per item on day 1 to 3.4s per item on day 14 is comparable to what has been reported in a previous diary study, where response times evolved from 5s per item on day 1 to 2-2.5s on day 30 of data collection (Arslan et al, 2020). Alongside these changes in the data, many participants reported becoming more habituated to the measures over time in interviews, as has been documented in one previous study (Paterson, Primeau, & Lauder, 2019).…”
Section: Changes In Response Behaviorsupporting
confidence: 87%
See 1 more Smart Citation
“…The predicted decrease from 4.4s per item on day 1 to 3.4s per item on day 14 is comparable to what has been reported in a previous diary study, where response times evolved from 5s per item on day 1 to 2-2.5s on day 30 of data collection (Arslan et al, 2020). Alongside these changes in the data, many participants reported becoming more habituated to the measures over time in interviews, as has been documented in one previous study (Paterson, Primeau, & Lauder, 2019).…”
Section: Changes In Response Behaviorsupporting
confidence: 87%
“…In the few studies that investigated reactive changes over time, researchers have mostly investigated linear changes in mean levels of variables (for exceptions, see Cruise et al, 1996;Zawadzki et al, 2019). However, this form may be inadequate, as it is possible that change manifests itself in an early stage of a study and flattens out over time (as suggested for example by Paterson, Primeau, &Lauder, 2019 andShrout et al, 2018) or that it appears only after a longer period of ESM. Additionally, there is indication that the perception of participants and the changes that can be detected in the data do not always converge (Aaron et al, 2005;Litt, Cooney, & Morse, 1998).…”
Section: The Role Of Individual Characteristics Study Design and The Operationalization Of Measurement Reactivitymentioning
confidence: 99%
“…Some studies describing feelings of being ‘devalued’ or ‘sidestepped’ by the health care system, and of ‘powerlessness’ and ‘isolation’ within the system (Chambers et al, 2018; Schildmeijer et al, 2019; Wennick et al, 2017). Men relayed concerns about having limited time in consultation with their HCP and in some cases a lack of access to specialist nurses (Catt et al, 2019; Paterson, et al, 2019). However, when specialist nurses were accessible, they were highly valued, with men reporting that they provided reassurance, understanding and a sense of hope that was otherwise absent (Hanly et al, 2014; Thera et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Participants described poor consistency of information between professionals at the same hospital (Catt et al, 2019; Dunn, Ralph et al, 2020) and also how seeing a different specialist on every visit led to a reluctance to discuss sensitive topics such as sexual health (Phahlamohlaka et al, 2018). Discharge to primary and community care also posed problems, with some receiving fragmented psychological and psychosexual support and survivorship care following discharge (Ettridge et al, 2017; Paterson et al, 2019; Wennick et al, 2017). Some men reported a lack of clarity about what discharge actually meant and about the ability of nonspecialists to address persistent health worries:…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation